Pertanggungjawaban Pidana terhadap Tindak Pidana Pencucian Uang oleh DNA Pro Trading Ditinjau dari Undang-Undang Nomor 8 Tahun 2010 tentang Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang - Muhammad Zidane; Chepi Ali Firman (Bandung Conference Series: Law Studies, 2024)
Abstract. This study aims to analyze the criminal liability for money laundering offenses committed by an investment company named DNA Pro Trading. The issues are analyzed based on Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes. The research method used is normative juridical with legislative and conceptual approaches. The data used are secondary data obtained from literature studies. The results of the study show that DNA Pro Trading can be held criminally liable for money laundering offenses based on Law Number 8 of 2010. This is because DNA Pro Trading was proven to have received, controlled, used, made an investment object, exchanged, or transferred, taken abroad, exchanged, or other acts concerning Assets that it knew or reasonably suspected were proceeds of crime. DNA Pro Trading can be subject to criminal sanctions of imprisonment, fines, and administrative sanctions in accordance with the applicable laws and regulations. people still exist, the implementation of Government Regulation in the Land No. 52 of 2014 Tengtang Guidelines for the Recognition and Protection of Indigenous Peoples has not been implemented by the Customary Rulers, the Head of Nagari Kapa Customary Affairs argued that with the enactment of the West Pasaman Regency Regulation No. 9 of 2017 concerning Nagari Customary Density, it has indicated that they are recognized by the state as a unit of Indigenous Peoples. Abstrak. Penelitian ini bertujuan untuk menganalisis pertanggungjawaban pidana terhadap tindak pidana pencucian uang yang dilakukan oleh perusahaan investasi bernama DNA Pro Trading. Permasalahan dianalisis berdasarkan Undang-Undang Nomor 8 Tahun 2010 tentang Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang.Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan dan konseptual. Data yang digunakan adalah data sekunder yang diperoleh dari studi kepustakaan. Hasil penelitian menunjukkan bahwa DNA Pro Trading dapat dikenakan pertanggungjawaban pidana atas tindak pidana pencucian uang berdasarkan Undang-Undang Nomor 8 Tahun 2010. Hal ini dikarenakan DNA Pro Trading terbukti menerima, menguasai, menggunakan, menjadikan objek investasi, menukarkan, atau mentransfer, membawa ke luar negeri, menukarkan, atau perbuatan lainnya atas Harta Kekayaan yang diketahuinya atau patut diduganya merupakan hasil tindak pidana. DNA Pro Trading dapat dikenakan sanksi pidana penjara, denda, dan sanksi administratif sesuai denganketentuan perundang-undangan yang berlaku.